Le collezioni egee del Museo Archeologico Nazionale di Firenze - JASINK, ANNA MARGHERITA; BOMBARDIERI, Luca (Cataloghi e collezioni, 2009)
The collection of Aegean exhibits in the National Archaeological Museum of Florence is of the greatest significance in terms of its richness and variety. The richness is illustrated by the quantity and value of the objects conserved, and the variety by a provenance and chronology of the artefacts that embrace pre-classical Aegean history practically in its entirety. This complete edition is organised on the basis of four main areas of provenance and production of the materials (Crete, Continental Greece, the Cyclades and Rhodes). The formation of the Florentine Aegean collections dates largely to the early twentieth century, and was the felicitous result of a combination of different circumstances. The most important of these was the commitment of Luigi Adriano Milani, Director of the nascent Royal Museum, to whom we owe the initial stimulus for a museum collection that could assume exemplary importance and respond to educational requirements. On line Database: www.fupress.net/collezioniegee